A Study Between Tawhid And Pluralism In Buya Hamka And Nurcholish Madjid's Interpretation Of Kalimatun Sawa In A Comparative Review - Azmil Iman Hartafan; Andri Nirwana AN (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2024)
This article attempts to explain the sentence sawa in interfaith. This concept needs to be further researched because it is anticipated as one of the approaches to inter-religious relations. Kalimatun sawa is a concept that comes from the Koran, namely Surah Ali Imran: 64, which is often used in inter-religious relations. However, there is a difference of opinion from two well-known Indonesian intellectual figures, namely Buya Hamka and Nurcholish Madjid, because they believe that Kalimun Sawa is religious pluralism and there are those who think Kalimun Sawa is a concept that explains that Islam is the only religion that is approved by Allah. . This type of research leads to qualitative research which is based on library research, both print and digital. By using comparative analysis, the author will explain the views of the two intellectuals to be analyzed and compared to reveal their different thought patterns. According to Hamka, Kalimun Sawa is an invitation to the people of the book to return to monotheism in order to establish Islam as the only true religion, on the other hand, Nurcholish Madjid interprets Kalimun Sawa as an effort to unite religions on the same basis. The research results state that current research regarding the Kalimun Sawa concept is not comprehensive enough to develop Nurcholish Madjid's ideas as a whole. Nurcholish Madjid put forward the idea of ​​comprehensive theology, emphasizing Islamic universalism and the need for harmony between Islam, Indonesian culture and modernity. He believes Kalimun Sawa can become a common platform for various religions and contribute to the development of a multicultural model in interfaith relations in Indonesia. In closing, Buya Hamka and Nurcholish Madjid discussed the Kalimatun Sawa concept in the context of interreligious relations, but Nurcholish Madjid's synthetic theological ideas and the role of Kalimatun Sawa in introducing Multiculturalism were more comprehensive and relevant to contemporary Indonesia.